2020
DOI: 10.1002/jha2.62
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and socioeconomic indicators associated with survival of myeloid leukemias in Canada

Abstract: Understanding how patient‐reported quality of life (QoL) and socioeconomic status (SES) relate to survival of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) may improve prognostic information sharing. This study explores associations among QoL, SES, and survival through administration of the Euro‐QoL 5‐Dimension, 3‐level and Functional Assessment of Cancer Therapy‐Leukemia and financial impact questionnaires to 138 adult participants with newly diagnosed AML or MDS in a longitudinal, pan‐Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…44 And the utility value of patients with different hematological malignancies in multiple countries was included for sensitivity analysis, showing no impact on the cost-effectiveness analysis results. 41,[45][46][47][48][49] The results of cost-effectiveness analysis found that letermovir might be a cost-effective choice within the cost-effectiveness threshold in China. In addition, studies published in Italy, Hong Kong, and the United States found that letermovir is cost-effective for adult CMV-seropositive allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…44 And the utility value of patients with different hematological malignancies in multiple countries was included for sensitivity analysis, showing no impact on the cost-effectiveness analysis results. 41,[45][46][47][48][49] The results of cost-effectiveness analysis found that letermovir might be a cost-effective choice within the cost-effectiveness threshold in China. In addition, studies published in Italy, Hong Kong, and the United States found that letermovir is cost-effective for adult CMV-seropositive allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%